Effects of home environment and center-based child care quality on children's language, communication, and literacy outcomes - Pinto, A. I.; Pessanha, M.; Aguiar, C. (Early Childhood Research Quarterly, 2013)
This study examined the joint effects of home environment and center-based child care quality on children's language, communication, and early literacy development, while also considering prior developmental level. Participants were 95 children (46 boys), assessed as toddlers (mean age = 26.33 months; Time 1) and preschoolers (mean age = 68.71 months; Time 2) and their families. At both times, children attended center-based child care classrooms in the metropolitan area of Porto, Portugal. Results from hierarchical linear models indicated that home environment and preschool quality, but not center-based toddler child care quality, were associated with children's language and literacy outcomes at Time 2. Moreover, the quality of preschool classrooms moderated the association between home environment quality and children's language and early literacy skills - but not communication skills - at Time 2, suggesting the positive cumulative effects of home environment and preschool quality. Findings further support the existence of a detrimental effect of low preschool quality on children's language and early literacy outcomes: positive associations among home environment quality and children's developmental outcomes were found to reduce substantially when children attended low-quality preschool classrooms.